Harmonic Analysis of Fuzzy Logic Controller Based Active Filter Unit Using Resonant Current Control in Distributed Power System - B, Pattabhiram.; Veerraju. M, Sai (International Journal of Engineering and Technology, 2018)
Wide-ranging utilize of nonlinear loads creates harmonic resonance issues in radial distribution system. Harmonic     amplification occurring at different locations in the radial line are due to the behavior of active filter as a harmonic admittance rather conductance. This paper presents fuzzy logic controlled active filter by using resonant current control to damp a harmonic resonance. For controlling active filter as an approximately pure harmonic conductance, collections of different parallel band-pass filters are tuned for resonant current controller at harmonic frequencies. A MATLAB/SIMULINK results illustrate that the fuzzy logic controller based active filter improves higher damping performance correlated with alternative techniques.